REMARKS AND CORRECTIONS TO THE STANDARD ISO 6336 - Miloš NĚMČEK (Scientific Journal of Silesian University of Technology. Series Transport)
The standard ISO 6336 for the calculation of load capacity of spur and helical gears was introduced in 2006. There were some later amendments, but several typographical and other errors. These can cause some misunderstandings during applications of the standard and are irritating for its users. This contribution seeks to highlight some aspects of the use of this standard, as well as drawing users’ attention to the errors it contains and, at the same time, properly worded content. To fully appreciate this article, the reader is advised to have a copy of the standard itself. Parts 3 and 6 of the standard are covered in the contribution.